Nicotinamide mononucleotide supplementation enhances aerobic capacity in amateur runners: a randomized, double-blind study - Bagen Liao; Yunlong Zhao; Dan Wang; Xiaowen Zhang; Xuanming Hao; Min Hu (Taylor & Francis Group, 2021)
Background Recent studies in rodents indicate that a combination of exercise training and supplementation with nicotinamide adenine dinucleotide (NAD+) precursors has synergistic effects. However, there are currently no human clinical trials analyzing this. Objective This study investigates the effects of a combination of exercise training and supplementation with nicotinamide mononucleotide (NMN), the immediate precursor of NAD+, on cardiovascular fitness in healthy amateur runners. Methods A six-week randomized, double-blind, placebo-controlled, four-arm clinical trial including 48 young and middle-aged recreationally trained runners of the Guangzhou Pearl River running team was conducted. The participants were randomized into four groups: the low dosage group (300 mg/day NMN), the medium dosage group (600 mg/day NMN), the high dosage group (1200 mg/day NMN), and the control group (placebo). Each group consisted of ten male participants and two female participants. Each training session was 40-60 min, and the runners trained 5-6 times each week. Cardiopulmonary exercise testing was performed at baseline and after the intervention, at 6 weeks, to assess the aerobic capacity of the runners. Results Analysis of covariance of the change from baseline over the 6 week treatment showed that the oxygen uptake (VO2), percentages of maximum oxygen uptake (VO2max), power at first ventilatory threshold, and power at second ventilatory threshold increased to a higher degree in the medium and high dosage groups compared with the control group. However, there was no difference in VO2max, O2-pulse, VO2 related to work rate, and peak power after the 6 week treatment from baseline in any of these groups. Conclusion NMN increases the aerobic capacity of humans during exercise training, and the improvement is likely the result of enhanced O2 utilization of the skeletal muscle. Trial registration number ChiCTR2000035138.